PENGEMBANGAN MODEL LITERASI DIGITAL DALAM PEMBELAJARAN KITAB KUNING DI MA’HAD AL-JAMIAH UIN MAULANA MALIK IBRAHIM MALANG - Muhammad Yasin Fatchul Barry (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2020)
Development of digital literacy is needed not only in formal education, but also for non-formal education such as pesantren. Therefore this study aims to describe the pattern of digital literacy development among ma'had al-jamiah students of Maulana Malik Ibrahim State Islamic University of Malang, as well as to explain the effectiveness of the use of the yellow book digital literacy model. This study uses the modified Borg and Gall R&D method, and the type of experimental research carried out to determine the effectiveness of product use. This research results in exposure to digital literacy in the ma'had that has been developed and the use of digital literacy of the yellow book through an android application that has a significant effect in increasing the ability of students to study the yellow book.